The Evolving Wage Structure of Young Adults in Australia: 2001 to 2019 - Birch, Elisa R.; Preston, Alison C (My University, 2021)
Using data from the Household, Income and Labour Dynamics in Australia (HILDA) survey together with OLS and quantile regressions, this paper examines the changing returns to education and the evolving wage structure of young adults (aged 25–34 years) between 2001 and 2019. Estimates show that real wage growth was strong for both males and females over the 2000s, underpinned by wage structure effects. Between 2010/11 and 2018/19 wage growth was flat (zero) for males and subdued for females. Institutional factors are thought to underpin the growth in wages of low-paid females over recent years, while education investments underpin recent wage growth amongst high-paid females. Since 2001/2 the wage premium on a degree qualification has declined for males and females. There has been no change in the adjusted gender wage gap across successive cohorts of 25–34 year olds.
Economic Record
Keywords: Adolescents and youth; Income, wealth and finances; Labour market